Dialog theory for critical argumentation - Walton, Douglas N. (Controversies, 2007)
Because of the need to devise systems for electronic communication on the internet, multi-agent computing is moving to a model of communication as a structured conversation between rational agents. For example, in multi-agent systems, an electronic agent searches around the internet, and collects certain kinds of information by asking questions to other agents. Such agents also reason with each other when they engage in negotiation and persuasion. It is shown in this book that critical argumentation is best represented in this framework by the model of reasoned argument called a dialog, in whi.